3(u-2)+5=2(3u-5)

Simplify each term.

Apply the distributive property.

3u+3⋅-2+5=2(3u-5)

Multiply 3 by -2.

3u-6+5=2(3u-5)

3u-6+5=2(3u-5)

Add -6 and 5.

3u-1=2(3u-5)

3u-1=2(3u-5)

Apply the distributive property.

3u-1=2(3u)+2⋅-5

Multiply.

Multiply 3 by 2.

3u-1=6u+2⋅-5

Multiply 2 by -5.

3u-1=6u-10

3u-1=6u-10

3u-1=6u-10

Subtract 6u from both sides of the equation.

3u-1-6u=-10

Subtract 6u from 3u.

-3u-1=-10

-3u-1=-10

Add 1 to both sides of the equation.

-3u=-10+1

Add -10 and 1.

-3u=-9

-3u=-9

Divide each term in -3u=-9 by -3.

-3u-3=-9-3

Cancel the common factor of -3.

Cancel the common factor.

-3u-3=-9-3

Divide u by 1.

u=-9-3

u=-9-3

Divide -9 by -3.

u=3

u=3

Solve for u 3(u-2)+5=2(3u-5)